Comparison between bupivacaine-lidocaine, dexamethasone mixture and bupivacaine alone for motor recovery after axillary brachial plexus block in distal radius surgery: A prospective randomized trial - Rawee Jongkongkawutthi; Paweenus Rungwattanakit; Pathom Halilamien; Suppachai Poolsuppasit; Busara Sirivanasandha (PLoS ONE, 2025)
Background Prolonged motor block, known as “dead arm,” which can cause patient discomfort and anxiety, is a serious concern that is often overlooked in ambulatory surgery, particularly in elderly patients. The purpose of this study was to examine the recovery time of motor blockade with bupivacaine and a mixture of bupivacaine-lidocaine-dexamethasone in axillary brachial plexus block. Methods A prospective, randomized, double-blinded controlled trial was conducted with 70 patients scheduled for distal end radius fixation under axillary brachial plexus block. A local anesthetic mixture group (LA-mixture group) received a 21 ml mixture of 0.2% bupivacaine with 1.2% lidocaine and 5 mg of dexamethasone (n =  35). A bupivacaine group received 20 ml of 0.5% bupivacaine with 1 ml of normal saline (n =  35). The primary outcome was the duration of the motor blockade. Secondary outcomes included the duration of sensory blockade, postoperative pain score, and the incidence of rebound pain. Results The demographic data were similar between the two groups. The mean times for recovery of hand grips and sensation were 13.5 ±  7.3 and 12.6 ±  6.2 hours in the LA-mixture group and 15.3 ±  6.7 and 14.6 ±  6.2 hours in the bupivacaine group. Pain scores were not significantly different between the two groups, but the incidence of rebound pain was lower in the LA-mixture group (8.6% and 28.6%, p =  0.031). Conclusion The bupivacaine-lidocaine, dexamethasone mixture failed to enhance motor recovery compared to 0.5% bupivacaine alone. However, patients in the mixture group appeared to experience a lower incidence of rebound pain. Trial registration Thai Clinical Trials Registry TCTR20200114003